2019
DOI: 10.1681/asn.2018121256
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Racial Disparities of Palliative Care Use among Hospitalized Patients with ESKD on Dialysis

Abstract: BackgroundStudy findings show that although palliative care decreases symptom burden, it is still underused in patients with ESKD. Little is known about disparity in use of palliative care services in such patients in the inpatient setting.MethodsTo investigate the use of palliative care consultation in patients with ESKD in the inpatient setting, we conducted a retrospective cohort study using the National Inpatient Sample from 2006 to 2014 to identify admitted patients with ESKD requiring maintenance dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 49 publications
(64 reference statements)
0
46
2
Order By: Relevance
“…Supported by existing literature, racial minority groups consistently report low educational literacy regarding palliative care, hospice care, and advance care planning, which leads to lower levels of engagement in advance care planning and discussions with health care providers. 1,15,16 Additionally, minorities are more likely than non-Hispanic Whites to receive palliative care services 17 and report less satisfying outcomes when completing an advanced directive. 15 It should be acknowledged that racial disparities may be a major contributor in the access and completion of advance directives, and knowledge and awareness deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by existing literature, racial minority groups consistently report low educational literacy regarding palliative care, hospice care, and advance care planning, which leads to lower levels of engagement in advance care planning and discussions with health care providers. 1,15,16 Additionally, minorities are more likely than non-Hispanic Whites to receive palliative care services 17 and report less satisfying outcomes when completing an advanced directive. 15 It should be acknowledged that racial disparities may be a major contributor in the access and completion of advance directives, and knowledge and awareness deficits.…”
Section: Discussionmentioning
confidence: 99%
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%
“…Overwhelming evidence, based on large national data sets, consistently and unequivocally points to major disparities in palliative care in the United States. 13 , 39 , 40 , 55 , 64 One retrospective cohort study of over 5 million hospitalizations of dialysis patients revealed that non-Hispanic Black and Hispanic patients were less likely than non-Hispanic White patients to receive palliative care services in the hospital. This disparity was observed in all hospital subtypes, even hospitals with a high proportion of minority patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Further, many a researcher has built an academic career pointing out these disparities, without ever suggesting real ways to overcome them. In this issue of JASN, Wen et al 3 provide us with yet another example.…”
mentioning
confidence: 99%